2019
DOI: 10.1111/jcmm.14420
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib attenuates renal interstitial fibrosis in kidney transplantation via regulating the EMT induced by TNF‐α‐Smurf1‐Akt‐mTOR‐P70S6K pathway

Abstract: Allograft interstitial fibrosis was characterized by massive extracellular matrix deposition caused by activated fibroblasts and myofibroblasts. Epithelial‐mesenchymal transition (EMT) is recognized as an important source of myofibroblasts contributing to the pathogenesis of allograft interstitial fibrosis. Smad ubiquitination regulatory factor 1 (Smurf1) has been recently reported to be involved in the progression of EMT. Our study was to detect the effect of Bortezomib and Smurf1 in the EMT and allograft int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…These alterations were accompanied with a notably increased expression of mesenchymal markers (α-SMA, collagen I, FSP-1 and vimentin), and a decreased expression of E-cadherin. These results are in agreement with previous studies (35)(36)(37). Interestingly, BMP-7 overexpression prevented this transformation from an epithelial to mesenchymal phenotype when treated with TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
“…These alterations were accompanied with a notably increased expression of mesenchymal markers (α-SMA, collagen I, FSP-1 and vimentin), and a decreased expression of E-cadherin. These results are in agreement with previous studies (35)(36)(37). Interestingly, BMP-7 overexpression prevented this transformation from an epithelial to mesenchymal phenotype when treated with TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
“…Interstitial fibrosis is the key characteristics in chronic renal allograft injury (Boor and Floege, 2015; Bontha et al, 2017). In the chronic renal allograft injury, diverse ranges of immune and nonimmune responses cause the macrophages to undergo macrophage-to-mesenchymal transition (MMT) process (Wang et al, 2019; Zhou et al, 2019). Higher rate of MMT contributes in the development of interstitial fibrosis (Wang et al, 2017).…”
Section: Mmt In Renal Fibrosismentioning
confidence: 99%
“…In our article, we also found that the impact of STRIP2 on LUAD cell invasion and migration was possibly regulated by EMT. EMT is a vital process in embryonic upgrowth and tumor migration . The invasion and migration ability of tumor cells are obviously heightened after the incidence of EMT .…”
Section: Discussionmentioning
confidence: 99%